Water and Chlorophyll Content and Leaf Anatomy of Patchouli Planlet (Pogostemon cablin Benth.) Resulted by Shoot-tip Culture Experience Hyperhydricity after Treatment of Modification Ammonium nitrate or Macro salt Concentration on MS medium (Murashige Skoog) - Zen, Aisyah Rahmawati; Widoretno, Wahyu; Indriyani, Serafinah (Graduate School, Universitas Brawijaya, 2016)
Hyperhydricity is a symptom of abnormal morphological and physiological function which inhibits the regeneration of plantlets. In general, the main symptom of hyperhydricity is a change in the condition of the plantlets which looks clear (Glassy) as a result of low levels of chlorophyll, the high water content in the plantlets, and the abnormal anatomical structure of the leaves. Hyperhydricity can be controlled by reducing cytokinin concentration, increasing gelling agent concentration, and reducing ammonium nitrate and macro salt concentration on medium. Objective of this research was to reduce hyperhydricity in shoot tip culture of patchouli by modification of ammonium nitrate and macro salt concentration on MS medium. The various treatment concentrations of ammonium nitrate were 0 mg.L-1 (0), 41.25 mg.L-1 (¼ concentration), 825 mg.L-1 (½ concentration), 1650 mg.L-1 (1 concentration) and macro salt MS with 0, ¼ MS, ½ MS, MS with 5 replications. Hyperhydricity on patchouli shoots could be lowered, as indicated by the decrease in water content from 96% to 90-91%, the increase in total chlorophyll content, and the increased number of palisade cells and stomata on the leaf treatment outcome. The concentration treatment of ammonium nitrate showed better results than the concentration of macros salt in increasing the total chlorophyll content, but it did not differ significantly in lowering water levels and increasing the number of palisade cells and stomata. ¼x concentration treatment of ammonium nitrate could increase chlorophyll content of 0.16 to 0.97 mg.g-1, but MS with 1x concentration showed the best result in the increase of number of palisade cells and stomata of the leaves. Keywords: Ammonium nitrate, Hyperhydricity, Macro Salt, Shoot-tip culture.